2003
DOI: 10.1016/s1097-2765(03)00264-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Actin-Related Proteins in ATP-Dependent Chromatin Remodeling

Abstract: Actin-related proteins (Arps) and conventional actin are enigmatic components of many chromatin-remodeling enzyme complexes. The yeast INO80 ATP-dependent chromatin-remodeling complex contains stoichiometric amounts of Arp4, Arp5, Arp8, and actin. Here we have revealed functions of Arp5 and Arp8 by analysis of mutants. arp5 Delta and arp8 Delta mutants display an ino80 Delta phenotype. Purification of INO80 complexes from arp5 Delta and arp8 Delta cells shows that protein complexes remain intact but are compro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
377
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 326 publications
(408 citation statements)
references
References 36 publications
(6 reference statements)
24
377
1
1
Order By: Relevance
“…Recently, it was shown by the Dutta group that Rvb proteins are essential for the chromatin remodeling activity of INO80.com [17]. They further found that loss of Rvb proteins leads to the loss of Arp5, a functionally important subunit of INO80.com [10]. Their in vitro studies reveal that Rvbs and Arp5 associate in a complex and the interaction is Ino80 and ATP dependent [17].…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Recently, it was shown by the Dutta group that Rvb proteins are essential for the chromatin remodeling activity of INO80.com [17]. They further found that loss of Rvb proteins leads to the loss of Arp5, a functionally important subunit of INO80.com [10]. Their in vitro studies reveal that Rvbs and Arp5 associate in a complex and the interaction is Ino80 and ATP dependent [17].…”
Section: Introductionmentioning
confidence: 98%
“…Despite increasing evidence suggesting that actin is in the nucleus and may play roles in many nuclear functions, the research on nuclear actin has been stalled by the lack of unambiguous demonstrations of an actin function in the nucleus both in vivo and in vitro. Previous studies appear to suggest that the INO80 complex contains a sub-complex consisting of actin, Arp4, Arp8 and Taf14, that associating with the ΔN domain [10] of the Ino80 ATPase. Interestingly, all subunits of this actin/Arp sub-complex, including the ΔN domain of the Ino80 ATPase are evolutionarily conserved, suggesting that this sub-complex represents a unique and evolutionarily conserved module used throughout the yeast INO80 complex and orthologous INO80 complexes in higher organisms.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations